Employer and internal branding research: a bibliometric analysis of 25 years - Saini, Gordhan K.; Lievens, Filip; Srivastava, Mukta (The journal of product & brand management, 2022)
Purpose In the past 25 years, employer and internal branding have grown significantly. Prior reviews tended to focus on either one of these domains. This study aims to map the intellectual structure of research on both employer branding and internal branding, thereby identifying impactful authors and journals, current and evolving themes and avenues for future research. Design/methodology/approach Using VOSviewer and Biblioshiny software packages, a bibliometric analysis of 739 articles was conducted using various methods such as citation analysis, bibliographic coupling, cluster analysis, keyword analysis and three-field plot. The Scopus results were further validated using 297 articles produced by the Web of Science data set. It ensured the robustness of the results and generalizability of the findings across bibliometric data sets. Findings The findings first report the impactful articles, authors and institutions of employer and internal branding research, along with popular keywords used in this area. Next, the analysis reveals four major clusters and seven subthemes (i.e. employer brand and job seekers, employer brand and employees, employer brand and international human resource management (HRM), third-party employer branding, internal branding – conceptualization/review, internal branding – antecedents and consequences, internal brand management). Early research focused more on “corporate brandings,” whereas current research deals more with “employer branding: antecedents and consequences,” “employer branding conceptualization/review,” and “internal branding” and its subthemes. The employer and internal branding clusters have evolved largely independent from each other. This study offers future research directions and practical implications per cluster. Originality/value To the best of the authors’ knowledge, this study is the first comprehensive bibliometric analysis of both employer and internal branding research.